2014
DOI: 10.4236/snl.2014.42006
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Situ</i> Preparation of Core Shell-Polypyrrole /Poly (Acrylonitrile-Co-Vinyl Acetate) Nanoparticles and Their Nanofibers

Abstract: Poly (acrylonitrile-co-vinyl acetate)/polypyrrole composite particles with uniform size and morphology have been synthesized using one-step polymerization that involves swelling and coating of polypyrrole (PPy) into P (AN-co-VAc) latex nanoparticles. As an initial stage, free radical copolymerization of acrylonitrile (AN) and vinyl acetate (VAc) was synthesized by emulsion polymerization using ammonium persulfate (APS) and dodecyl benzene sulfonic acid salt (DBSA) as a surfactant. P (AN-co-VAc)/PPy composites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Synthesis of P(AN-co-IA) copolymer and PAN homopolymer P(AN-co-IA) copolymer was synthesized by emulsion polymerization utilizing water, SDBS and APS as dispersion medium, surfactant, and initiator, respectively. The polymerization was lasted for 3 h at 70 C and then stopped using ethanol and then cooled to room temperature as in previous studies [41][42][43]. The obtained emulsion latex was precipitated and washed with ethanol and water for five times.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Synthesis of P(AN-co-IA) copolymer and PAN homopolymer P(AN-co-IA) copolymer was synthesized by emulsion polymerization utilizing water, SDBS and APS as dispersion medium, surfactant, and initiator, respectively. The polymerization was lasted for 3 h at 70 C and then stopped using ethanol and then cooled to room temperature as in previous studies [41][42][43]. The obtained emulsion latex was precipitated and washed with ethanol and water for five times.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…In a study, Unsal et al [10] copolymerized AN with butylacrylate and pyrrole; they showed that by incorporation of butylacrylate to the system, the mechanical properties of the resulting polymer improved. Copolymerization of P(AN-co-IA)-polypyrrole was achieved by Arman and Sarac [14] via emulsion polymerization for the synthesis of AN and vinylacetate in order to investigate the morphology of the nanocomposites. Bhanu et al [11] used methylacrylate for copolymerizing with AN and they carried out synthesis and characterization of the produced polymer.…”
Section: Introductionmentioning
confidence: 99%